1928
DOI: 10.1021/ja01398a009
|View full text |Cite
|
Sign up to set email alerts
|

III. THE REVERSIBLE ADDITION OF ETHYL ALCOHOL TO PARA-BROMOBENZONITRILE CATALYZED BY SODIUM, POTASSIUM AND LITHIUM ETHYLATES1

Abstract: The circumstances of the first determination of the isotopes of lead are given.Washington, D. C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1934
1934
1972
1972

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Various attempts were made to increase the accuracy of the method by reducing the liquid-junction potential to small values and by the use of cells without liquid junction 19,10,11,12).…”
Section: Dissociation Constants From Cells Without Liquid Junctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various attempts were made to increase the accuracy of the method by reducing the liquid-junction potential to small values and by the use of cells without liquid junction 19,10,11,12).…”
Section: Dissociation Constants From Cells Without Liquid Junctionmentioning
confidence: 99%
“…pK~= (E-EO)/k+log(mH2Po4mct!mHPo4)+2A-J;, (10) where A is a constant for aqueous solutions at a particular temperature. Values of pK; from eq 10 approach the true value of pK2 in .dilute solutions.…”
Section: 3026rt/fmentioning
confidence: 99%
“…Another possibility that may account for the lack of constancy of the emf [15] is the age of the hydrogen and calomel electrodes. It has been shown [18,19,20,21] that if these electrodes are not sufficiently aged, they will give different potentials in solutions of the same composition. Smith and Taylor [22] have likewise shown that if silver-silver-chloride electrodes are not sufficiently aged, new electrodes will act as cathodes toward aged ones when immersed in a chloride solution and that periods as long as 1 week may be required for attainment of a common potential.…”
Section: Hyd1'ogen Electrodes In Phthalate Solu!tionsmentioning
confidence: 99%
“…Many of the studies in reaction kinetics which led Aeree (263,371,279) to favor the "dual theory" of catalysis were concerned with alkali alkoxides.…”
Section: Catalytic Effectsmentioning
confidence: 99%